Acupuncture in addition to standard conservative treatment for overactive bladder; a feasibility trial for a randomized controlled study. Issue 7 (21st July 2021) - Hargreaves, Emma; Harding, Chris; Clarkson, Carl
Abstract: Aims: This study aims to assess the feasibility of an randomized controlled trial (RCT) to test treatment efficacy of acupuncture for symptoms of overactive bladder syndrome (OAB), a common long‐term condition with physical, psychological, social and sexual consequences. Methods: A total of 30 participants were recruited and randomized to either standard conservative management for OAB or standard conservative management plus acupuncture. Standard care consisted of individually tailored advice regarding bladder health, pelvic floor exercises and lifestyle adjustments. The intervention group received 6 sessions of acupuncture over an 8‐week period. Outcomes measured included adherence to the study protocol, recruitment rate, participant attrition rate and adverse events. A 3‐day bladder diary and Incontinence Questionnaire—short form questionnaire were used to assess symptoms. The ICEpop CAPability measure for Adults measure was used to assess well‐being. Outcomes were collected at baseline, after 8 weeks of intervention and 6 weeks after completing intervention. An exit questionnaire captured participant experience data. Results: Comparison of the two groups at baseline did not detect statistically significant differences in demographics and symptom profile. A total of 23 participants completed all study proceedures. Recruitment was completed in 11 months, quicker than anticipated. No serious adverse events occurred; minor adverse events were recorded in 11/114 (9.6%) treatments. A total of seven participants failed to complete one or more study proceedures with an overall attrition rate of 23.3%. Conclusions: Most participants completed all aspects of the study and found the protocol acceptable. The interventions appear safe and well tolerated. The concept of a large‐scale RCT with a similar protocol was proven and appears feasible based on this pilot work.